Linalool effect on mitochondrial bioenergetics rat liver - BUENO-DUARTE, Yenny; MÉNDEZ-SÁNCHEZ, Stelia Carolina (Vitae, 2015)
Background: The linalool (2,6-dimethyl-2 ,7-octadiene-6-ol) is a monoterpene present in more tan 200 types of plants, and it is the major component of several essential oils. The linalool has a wide range of potential pharmacological properties, such as antiseptic, anxiolytic, anti-inflammatory, antifungal, antimicrobial and proapoptotic in different tumor cell lines. However, its primary use is associated as an odorant molecule or fragrance in topical products, in cosmetics products and fragrance industry. Objective: In this study the effect of linalool on the bioenergetics of isolated rat liver mitochondria was evaluated. Methods: Linalool in concentrations between (5-100μg/mL) was evaluated in isolated mitochondria of male albino Wistar rats, according to the method described by Voss et al (1961). Initially, the oxygen consumption by intact mitochondria was determined by polarographic method using an oxygraph. Subsequently, the effect of the compound on mitochondrial respiratory chain enzymes was evaluated, by using polarographic and spectrophotometric methods. Results: The results obtained indicated that linalool, at concentrations of 5, 10, 50 and 100μg/mL, affects the rate of oxygen consumption in state 3 and 4 of mitochondria energized with glutamate-malate and succinate. However, the inhibitory effect was greater when using glutamate-malate as substrate. For its part, the analysis of the enzyme activities of the mitochondrial respiratory chain showed that linalool (50μg/mL) inhibits complex I, III, and ATPase activity. Conclusions: linalool inhibits complex I, complex III and ATPase, this inhibition could increase the generation of reactive oxygen species.